Music, Movement, and Mind: Use of Drumming to Improve Strength, Balance, Proprioception, Stamina, Coordination, and Emotional Status in a 12-Year-Old With Agenesis of the Corpus Callosum: A Case Study. (June 2020) - Spak, David; Card, Elizabeth
The purpose of this article is to report a case study of the effect of therapeutic drumming on motor, communication skills, and behavior of a preteen diagnosed with agenesis of the corpus callosum. This 12-year-old participated in 30- to 45-minute weekly sessions over a 12-month period in which rudimentary drumming exercises were used to analyze and then measure any changes in equilibrium reactions, postural transfers, and trunk control. Measurable documentation evidenced marked improvement in motor skills while suggesting communication and behavioral improvement. The findings support the theory that therapeutic drumming would benefit preteens with agenesis of the corpus callosum, which provides promising evidence to other neurologic developmental diagnoses and therefore indicates a need for further research. While the therapeutic nature of music is well documented, how the listener participates can influence the effect of the music. For example, passive music listening can improve pain or anxiety, however, active music listening with expected intentional action may improve physical, mental, behavioral, and spiritual healing. Active music listening could be a valuable holistic nursing intervention.